New-onset paroxysmal atrial fibrillation in acute myocardial infarction: increased risk of stroke - Si-Hyuck Kang; Chang-Hwan Yoon; Dong-Ju Choi; Ji Hyun Lee; Jin Joo Park; Tae-Jin Youn; In-Ho Chae; Sun-Hwa Kim; Wonjae Lee; Youngjin Cho; IL-Young Oh; Jung-Won Suh; et al. (BMJ Open)
Objective To investigate the long-term prognostic implications of transient new-onset atrial fibrillation (AF) in patients with acute myocardial infarction (AMI).Design Retrospective observational study.Setting Single tertiary centre.Participants This study included 2523 patients who presented with AMI from 3 June 2003 to 24 February 2015, after the exclusion of those with prior AF or in-hospital death.Outcome measures Patients were divided into three groups according to the occurrence and type of new-onset AF: (1) sinus rhythm (SR) group; (2) paroxysmal AF (PaAF: AF converted to SR prior to discharge) group and (3) persistent AF (PeAF: AF persisted during the hospitalisation) group. Post-discharge all-cause mortality and stroke incidences were compared between the groups.Results New-onset AF was observed in 271 patients (10.7%; PaAF: 230, PeAF: 41). The median follow-up period was 7.2 years (IQR: 5.2–9.4). The incidence of all-cause death and stroke was highest in the PeAF group, followed by the PaAF and SR groups (all-cause mortality: 48.8% vs 26.5% vs 14.7%, p<0.001; stroke 22.0% vs 8.3% vs 4.4%, p<0.001). In the multivariable analysis, PaAF and PeAF were associated with an increased risk of stroke (PaAF, HR: 1.972, 95% CI: 1.162–3.346; PeAF, HR: 5.160, CI: 2.242–11.873) compared with SR. The PaAF group showed a higher incidence of post-discharge AF than the SR group (29.1% vs 4.2%, p<0.001).Conclusions New-onset AF following AMI is associated with poor long-term outcomes. Even when AF episodes are brief and are converted to SR, new-onset AF remains associated with an increased risk of recurrent AF and stroke.